Multi-Attribute Decision Making Dalam Pemilihan Lampu Pada Sistem Pencahayaan Lapangan Badminton - Wiwien Hadikurniawati; Imam Husni Al Ami (Universitas PGRI Semarang, 2016)
Light is essential for daily human activities. The main function of the lightingsystem is to provide a safe environment visually, ease in completing the work visually and toprovide a comfortable and pleasant visual environment. The lighting system in sports arena isimportant because it affects the visual comfort of the people who are exercising and spectatorsat the sports arena. Selection of types and specifications required lamps used to analyze the level of lighting needs in the sports court. Multi-attribute decision making (MADM) determinesthe type of lamps used in sports arena, especially for lighting badminton court. AnalyticHierarchy Process (AHP) is one of the MADM methods used to analyze the parameters andcriteria for decision making. Some of the parameters used as the calculation in the choice oflights on a sports arena, especially for badminton is powerful calculations lighting (Lux), thecalculation of power (watts), the calculation of electrical power per meter wide field,computation of luminous efficacy (Lm / watt), color temperature, operating costs andmaintenance costs.